The value proposition of the Global Health Security Index. Issue 10 (8th October 2020) - Ravi, Sanjana J; Warmbrod, Kelsey Lane; Mullen, Lucia; Meyer, Diane; Cameron, Elizabeth; Bell, Jessica; Bapat, Priya; Paterra, Michael; Machalaba, Catherine; Nath, Indira; Gostin, Lawrence O; James, Wilmot; et al.
Abstract : Infectious disease outbreaks pose major threats to human health and security. Countries with robust capacities for preventing, detecting and responding to outbreaks can avert many of the social, political, economic and health system costs of such crises. The Global Health Security Index (GHS Index)—the first comprehensive assessment and benchmarking of health security and related capabilities across 195 countries—recently found that no country is sufficiently prepared for epidemics or pandemics. The GHS Index can help health security stakeholders identify areas of weakness, as well as opportunities to collaborate across sectors, collectively strengthen health systems and achieve shared public health goals. Some scholars have recently offered constructive critiques of the GHS Index's approach to scoring and ranking countries; its weighting of select indicators; its emphasis on transparency; its focus on biosecurity and biosafety capacities; and divergence between select country scores and corresponding COVID-19-associated caseloads, morbidity, and mortality. Here, we (1) describe the practical value of the GHS Index; (2) present potential use cases to help policymakers and practitioners maximise the utility of the tool; (3) discuss the importance of scoring and ranking; (4) describe the robust methodology underpinning country scores and ranks; (5) highlight the GHS Index's emphasis on transparency and (6) articulate caveats for users wishing to use GHS Index data in health security research, policymaking and practice.